2013
DOI: 10.1007/s10877-013-9498-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac output assessed by non-invasive monitoring is associated with ECG changes in children with critical asthma

Abstract: The primary aim of this study was to determine changes in CI and SI, if any, in children hospitalized with status asthmatics during the course of treatment as measured by non-invasive EC monitoring. The secondary aim was to determine if there is an association between Abnormal CI (defined as <5 or >95 % tile adjusted for age) and Abnormal ECG (defined as ST waves changes) Non-invasive cardiac output (CO) recordings were obtained daily from admission (Initial) to discharge (Final). Changes in CI and SI measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This device estimates CO, CI, stroke volume (SV), SI, and a variety of other cardiac parameters using a complex mathematical algorithm (electrical velocimetry relates the maximum rate of change of impedance to peak aortic blood acceleration during the cardiac cycle) with the simple application of four EKG electrodes . The accuracy of this monitor has been validated and compared with other measures of CO such as the Fick equation , thermodilution , and echocardiography in diverse pediatric populations including patients with congenital heart disease and critical illness , neonates , and obese adolescents . One study of patients who had recovered from critical illness demonstrated a bias toward underestimation of CI and another found it to be useful in patients who had undergone cardiac surgery .…”
Section: Discussionmentioning
confidence: 99%
“…This device estimates CO, CI, stroke volume (SV), SI, and a variety of other cardiac parameters using a complex mathematical algorithm (electrical velocimetry relates the maximum rate of change of impedance to peak aortic blood acceleration during the cardiac cycle) with the simple application of four EKG electrodes . The accuracy of this monitor has been validated and compared with other measures of CO such as the Fick equation , thermodilution , and echocardiography in diverse pediatric populations including patients with congenital heart disease and critical illness , neonates , and obese adolescents . One study of patients who had recovered from critical illness demonstrated a bias toward underestimation of CI and another found it to be useful in patients who had undergone cardiac surgery .…”
Section: Discussionmentioning
confidence: 99%
“…When the high rate (87%) of patients having reduced LV ejection fraction (EF) in the setting of TTS is taken into account, less than half of the patients (47%) presenting with dyspnea may seem relatively low. Nevertheless, this discrepancy is supported by the fact that patients with TTS frequently have a benign course despite losing >50% functional left ventricular myocardium while a patient with ACS faces death in loss of a similar sized portion of LV myocardium [5,17]. Nonetheless, it should be noted that in-hospital death rates are similar between patients with TTS and ACS.…”
Section: Historymentioning
confidence: 99%
“…Wong and colleagues in the same edition provided a more clinical report of cardiac output monitoring being used to study the progress of children admitted to a hospital for treatment of acute asthma [13]. The cardiac output monitor used was the Aesculon, or portable version the Icon (Cardiotronic Inc., La Jolla, CA, USA) a hybrid bioimpedance device.…”
Section: Evaluation Of Haemodynamic Alterations and Fluid Responsivenessmentioning
confidence: 99%